Real-time polymerase chain reaction methods for strain specific identification and enumeration of strain Lacticaseibacillus paracasei 8700:2 - Shehata, Hanan R.; Hassane, Basma; Newmaster, Steven G. (Frontiers in Microbiology, 2023)
Reliable and accurate methods for probiotic identification and enumeration, at the strain level plays a major role in confirming product efficacy since probiotic health benefits are strain-specific and dose-dependent. In this study, real-time PCR methods were developed for strain specific identification and enumeration of L. paracasei 8700:2, a probiotic strain that plays a role in fighting the common cold. The assay was designed to target a unique region in L. paracasei 8700:2 genome sequence to achieve strain level specificity. The identification method proved to be strain specific and to be highly sensitive with a limit of detection of 0.5 pg of DNA. The enumeration method was based on viability real-time PCR (v-qPCR) to quantify viable cells only. The optimal viability dye (PMAxx) concentration was 50 M. The method was found to be efficient (>90% with R2 values > 0.99), with a linear dynamic range between 6*102 and 6*105 copies. The method was highly precise with a relative standard deviation below 5%. The performance of the v-qPCR enumeration method was then compared to plate count (PC) method and viability droplet digital PCR (v-ddPCR) method. The Pearson correlation coefficient (r) was 0.707 for PC and v-qPCR methods, and 0.922 for v-qPCR and v-ddPCR. Bland-Altman method comparison showed that v-qPCR always gave higher values compared to PC method (relative difference ranging from 119% to 184%) and showed no consistent trend (relative difference ranging from -20% to 22%) when comparing v-qPCR and v-ddPCR methods. The difference between PC and v-PCR methods can potentially be attributed to the proportion of cells that exist in a viable but non culturable (VBNC) state, which can be count by v-PCR but not with PC. Since VBNC cells are considered probiotics, v-PCR methods would be more accurate than PC methods in determining viable counts. The developed v-qPCR method was confirmed to be strain specific, sensitive, efficient, with low variance, able to count VBNC cells, and has shorter time to results compared to plate count methods. Thus, the identification and enumeration methods developed for L. paracasei 8700:2 will be of great importance to achieve high quality and efficacious probiotic products.